Assistance in the Implementation of Integrative Holistic Early Childhood Education (Paud-Hi) and the Implementation of Balanced Nutrition in the Early Childhood Cluster in Talang Belido Village - Perdana, Silvia Mawarti; Ibnu, Ismi Nurwaqiah; Reskiaddin, La Ode; Solida, Adila; Eka Rini, Willia Novita (Abdi Masyarakat, 2024)
Optimal early childhood growth and development will determine their health status in the future. Implementing Integrative Holistic Early Childhood Education (PAUD-HI) is an effort to optimize children's growth and development by paying attention to various children's characteristics. Apart from that, implementing balance diet in early childhood is expected to be able to establish optimal nutritional status in children. PAUD Group 2 Bungo Selango, located in Sungai Gelam District, Muaro Jambi Regency, has not implemented PAUD-HI optimally due to various risk factors. Kindergarten teachers have never received early childhood balance diet education. This community service activity aimed to optimize the implementation of PAUD-HI and implement balance diet in PAUD Group 2 Bungo Selango. In this community service activity, they are given health education and demonstrations related to the application of balance diet in holistic and integrative kindergarten learning. The results of community service activities showed that there is an increase in target’s knowledge before and after being given education which is not significantly different (Sig.>0.05). It is necessary to get used to implementing balance diet (consuming variety of foods, physical activity, clean and healthy lifestyle, and controlling ideal body weight) in holistic and integrative kindergarten learning.